Does Vertebroplasty Cause Incident Vertebral Fractures? A Review of Available Data - Trout, A.T.; Kallmes, D.F. (American Journal of Neuroradiology, 2006)
SUMMARY: Vertebroplasty has been in practice in the United States for approximately 10 years and has been described as providing significant benefit to patients with painful vertebral compression fractures. Although the procedure appears to provide dramatic pain relief, it is not without complications. The primary point of discussion in this paper is whether vertebroplasty predisposes patients to the development of additional vertebral fractures, at a rate higher than that seen in the absence of vertebroplasty. To date there remains no definitive answer to this question. There is, however, a significant body of data available in the literature that relates to this issue. This review explores and attempts to synthesize the data both supporting and refuting a relationship between vertebroplasty and the development of subsequent fractures.